A soma das raízes das equações 3x - 6 = 0 e -5 x -10 = 0
a)4
b)2
c)1
d)0
Soluções para a tarefa
Respondido por
2
Resposta: d)0
Explicação passo-a-passo:
Respondido por
1
Resposta:
Alternativa d)
Explicação passo-a-passo:
3x - 6 = 0 ⇒ 3x = 6 ⇒ x = 6/3 ⇒ x = 2
-5x = 10 ⇒ -5x = 10 ⇒ x = 10/-5 ⇒ x = -2
2 + (-2) = 2 - 2 = 0
Alternativa d)
Perguntas interessantes
Matemática,
8 meses atrás
Artes,
8 meses atrás
Português,
8 meses atrás
Matemática,
10 meses atrás
Inglês,
10 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás